Analysis The Effect of College Student’s Perceptions on Investment to Their Interest on Investing in Stock Market - Viqar Azkiansyah (International Journal Administration, Business & Organization, 2022)
This study aims to determine how much influence of the student’s perception on investment has to student’s intrest on investing in Indonesian Stock Market (IDX). Respondents came from stundents college who live or study in Bandung city, this study uses quantitative descriptive methods, validity and reliability tests, an data analysis using simple linear regression. 100 respondents had been participate as sample of this study, data collection was done by distributing questionaire by google form. The result of this study showed that a positive perception of investment does have an effect to students intrest on investing in stock market